Combined landscape of single-nucleotide variants and copy number alterations in clonal hematopoiesis - Saiki, Ryunosuke; Momozawa, Yukihide; Nannya, Yasuhito; Nakagawa, Masahiro M.; Ochi, Yotaro; Yoshizato, Tetsuichi; Terao, Chikashi; Kuroda, Yutaka; Shiraishi, Yuichi; Chiba, Kenichi; Tanaka, Hiroko; Niida, Atsushi; et al. (Nature medicine, 2021)
Clonal hematopoiesis (CH) in apparently healthy individuals is implicated in the development of hematological malignancies (HM) and cardiovascular diseases. Previous studies of CH analyzed either single-nucleotide variants and indels (SNVs/indels) or copy number alterations (CNAs), but not both. Here, using a combination of targeted sequencing of 23 CH-related genes and array-based CNA detection of blood-derived DNA, we have delineated the landscape of CH-related SNVs/indels and CNAs in 11,234 individuals without HM from the BioBank Japan cohort, including 672 individuals with subsequent HM development, and studied the effects of these somatic alterations on mortality from HM and cardiovascular disease, as well as on hematological and cardiovascular phenotypes. The total number of both types of CH-related lesions and their clone size positively correlated with blood count abnormalities and mortality from HM. CH-related SNVs/indels and CNAs exhibited statistically significant co-occurrence in the same individuals. In particular, co-occurrence of SNVs/indels and CNAs affecting DNMT3A , TET2 , JAK2 and TP53 resulted in biallelic alterations of these genes and was associated with higher HM mortality. Co-occurrence of SNVs/indels and CNAs also modulated risks for cardiovascular mortality. These findings highlight the importance of detecting both SNVs/indels and CNAs in the evaluation of CH. Analysis of single-nucleotide variants and copy number alterations gives a more complete picture of clonal hematopoiesis and its impact on hematological malignancy and cardiovascular disease.